Desarrollo de una herramienta de cálculo para la determinación del costo nivelado de energía en el Contexto Ecuatoriano - Gavilema Orozco, Lilian Adriana (2022)
The energy cost (LCOE, for its acronyms in English) represents a constant value per generation unit and allows comparing the different technologies feasibility. The LCOE, also it allows assessing the different generation projects feasibility considered within the study, in order to make decisions based on production costs. The current research project has as object to determine the energy levelized cost, through the calculation tool development for the electricity generation different types in Ecuador. It has been taken into consideration the Electricity Regulation and Control Agency (ARCONEL) Resolution No. 037/19 methodology, since it embraces different regulations, methodologies and procedures already established and applied within the Ecuadorian context.